Feasibility of the book "Ragam Bahasa Hukum" as an Indonesian language teaching material in Law Study Program - Triwati Rahayu; Suryadi Suryadi (BAHASTRA, 2022)
Books are a component of teaching materials as learning tools. Indonesian language learning in the Law study program particularly needs textbooks whose feasibility is in accordance with the field of legal science. This study intends to contribute to the Indonesian language course textbooks in the Law study program. This study aims to describe the data on the feasibility of the content, language, and presentation of the book "Ragam Bahasa Hukum" (Legal Language). To achieve this aim, this study employed a descriptive qualitative approach with data sourced from the book "Ragam Bahasa Hukum". The data were analyzed using an interactive analysis model. The stages of the method began with data collection, data reduction, data presentation, and concluding. FGDs with linguists and legal experts were conducted to evaluate the books. The results of this study indicate that the book “Ragam Bahasa Hukum” (1) has a proper content/material with an average score percentage of 75%; (2) has presentation feasibility with an average score of 82%; (3) has linguistic feasibility with an average score of 75%; and (4) has graphic feasibility with an average score percentage of 80%. The textbook understudy is excellent in that it also examines the legal register. Based on the assessments of legal experts and linguistic experts, the book is feasible and categorized as good in terms of the completeness of the materials, suitability of examples, and the interrelationships between concepts.